Fifteen minute consultation: Managing neonatal and childhood herpes encephalitis. Issue 2 (11th August 2014) - Le Doare, K; Menson, Esse; Patel, Deepak; Lim, Ming; Lyall, Hermione; Herberg, Jethro
Abstract : Herpes simplex encephalitis (HSE) is the most common single cause of viral encephalitis in infants and children. Treated or untreated, it can be associated with considerable morbidity and mortality, and its presentation is usually insidious and non-specific. Prompt and careful investigation is important in order to establish the diagnosis so that treatment can be optimised. We address some common questions arising when diagnosing and treating presumed HSE throughout childhood.